Ruskin, the Theatre and Victorian Visual Culture
XIII, 242 p.
Keywords: This collection of essays sets out to challenge the dominant narrative about Victorian theatre by placing the practices and products of the Victorian theatre in relation to Victorian visual culture, through the lens of the concept of 'Ruskinian theatre', an approach to theatre which values its educative purpose as well as its aesthetic expression.